Analysis of the Concept of a Healthy Church Based on Acts 4:32 - Georges Nicolas Djone; Suwandi D; Toni Hutasoit; Lasino J.W. Putro; Abdon A. Amtiran (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to analyze the concept of a healthy church based on Acts 4:32 and its relevance to the Church today. The method used is qualitative exegesis and data collection through Bible sources, books, and journals that discuss topics as needed. This topic is necessary because many unhealthy churches are now full of divisions. The result: First, a healthy church has unity and unity among its congregations. The Church, in conclusion, is a spiritual institution and belongs to God in essence; it must be fit by showing the characteristics of oneness and unity in the community so that in this way, the Church can glorify the name of God.